Pengaruh Penggunaan Multimedia Storyboard Terhadap Hasil Belajar Nihonshi : (Penelitian Eksperimen pada Mahasiswa Semester II Jurusan Bahasa Jepang Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Prof. Dr. Hamka Jakarta) (Universitas Negeri Jakarta, 2018)
This study aims to determine the effect of storyboard multimedia toward Japanese history (nihonshi) learning result and to identify student’s response after learning Japanese history (nihonshi) by using storyboard multimedia. This research is true experiment using a pretest-posttest control group design. Samples are students of Japanese, totaling 31 students. 14 students as an experimental class and 17 students as a control class. Test and non-test instruments are used in data collection techniques. The results showed that the nihonshi learning result of experimental class has increased after using storyboard multimedia. It showed the effect of storyboard multimedia toward nihonshi learning result.